Small Noncoding 4.5SH and 4.5SI RNAs and Their Binding to Proteins - Tatosyan, K. A.; Koval, A. P.; Kramerov, D. A. (Molecular biology (New York), 2018)
— The functions of small noncoding RNAs 4.5SH and 4.5SI found in murine-like rodents are unclear. These RNAs synthesized by RNA polymerase III are widely expressed in rodent organs and tissues. Using crosslinking assays, it was shown that approximately half of all 4.5SI and 4.5SH RNA molecules were bound to proteins provisionally called X and Y, respectively. An immunoprecipitation experiment showed that both these RNAs were associated with the La protein, which did not crosslink to them. The termini of 4.5SI RNA form a long duplex stem, which makes the molecule more stable than 4.5SH RNA. Modification of the 5'-end sequence destructing the stem of 4.5SI RNA altered its protein-binding properties; after the 3'-end sequence was changed to the complementary, both the stem structure and the RNA binding to protein X were restored. Presumably, this protein plays a role in increasing the half-life of 4.5SI RNA.